The Utilization of Intelligent Traffic Systems for Managing Traffic Problems in Tourism Areas: A Literature Review - Hasby Ristama (Deviance Jurnal kriminologi, 2023)
This research aims to investigate the utilization of intelligent traffic systems (ITS) to address traffic issues in regions popular among tourists. The present study employs a literature review methodology to systematically analyze and compile diverse research findings about the utilization of technology in traffic engineering within tourist destinations. The results indicate that implementing intelligent transportation systems (ITS) can be viable for addressing traffic management challenges in tourist destinations. Integrating information and communication technology (ICT) can optimize traffic management, enhance transportation infrastructure, augment transportation coordination and management, and bolster traffic security in tourist destinations. The prescribed steps for implementing ITS involve conducting a thorough analysis of needs, devising, and designing an appropriate ITS solution, executing the implementation process, and operationalizing and maintaining the ITS system. The study's findings suggest that Intelligent Transportation Systems (ITS) hold significant promise for enhancing traffic management in tourist regions. Implementing suitable measures by Intelligent Transportation Systems (ITS) can effectively address traffic congestion, insufficient infrastructure, inadequate coordination, and safety concerns in managing traffic in tourist destinations. Furthermore, implementing Intelligent Transportation Systems (ITS) can enhance efficiency, safety, and the overall tourist experience while mitigating the environmental footprint of transportation systems in tourist destinations. The Intelligent Traffic System (ITS) is a traffic management solution that utilizes information and communication technology to enhance traffic flow and safety. ITS is particularly relevant in tourist areas where traffic congestion can be a significant issue.